The Right Turn in India: Authoritarianism, Populism and Neoliberalisation. Issue 4 (8th August 2018) - Chacko, Priya
ABSTRACT: This article argues that the growth of authoritarian forms of politics in India should be seen in the context of a long-term crisis of the state as successive governments have been unable to establish legitimacy for the policies of neoliberalisation that have been pursued since the 1990s. These policies contributed to the fracturing of dominant modes of political incorporation. The previous Congress Party-led government's mode of crisis management – which it dubbed, inclusive growth – failed to create new forms of political incorporation by addressing long-term structural problems in India's political economy, such as jobless growth, and gave rise to new problems, such as large-scale corruption scandals. Subsequently, it increasingly developed what Nicos Poulantzas called, "authoritarian statist" tendencies to marginalise dissent within a framework of constitutional democracy. The current Bharatiya Janata Party-led government's mode of crisis management builds on these authoritarian statist tendencies but has sought to build legitimacy for these tendencies and neoliberalisation through an appeal to authoritarian populism. This seeks to harness popular discontent against elite corruption with majoritarianism to create an antagonism between the "Hindu people" and a "corrupt elite" that panders to minorities.